Work-family conflict and family-work conflict in aspects of sex and intergenerational differences - Anna Sylwia Lubrańska (Nofer Institute of Occupational Medicine, 2014)
Background: This paper presents the results of the study concerning mutual relations between work-family conflict and family- work conflict in the context of age and sex. Material and Methods: The study included 223 subjects (115 women, 108 men, 74 mothers and 61 fathers), aged 21-63. The Work-Family and Family-Work Conflicts Questionnaire and socio-demographic questionnaire were used as the survey tools. To verify hypotheses the correlation analysis and the Mann-Whitney U-test were used. Results: It has been found that a stronger work-family conflict is experienced by the examined men and fathers and a stronger family-work conflict is observed among parents. The results of the statistical analysis showed that there is a significant relationship between the number of working hours per day and work-family conflict and family-work conflict. Work-family conflict among mothers is significantly correlated with the income. The family-work conflict is stronger in the middle adulthood group. Conclusions: There is a significant relationship between sex and age and work-family conflict and family-work conflict. Med Pr 2014;65(4):521-533